Eat something : a Wise Sons cookbook : for Jews who like food and food lovers who like Jews - Bloom, Evan; Levin, Rachel (Chronicle Books, 2020)
"Here is a cookbook for Jews who like food and food lovers who like Jews. From nationally recognized Jewish deli and Bay Area favorite, Wise Sons, this cookbook presents over 50 recipes for salads, soups, baked goods, holiday dishes, and more from their beloved restaurants. Recipes are organized into 20 occasions that chronicle a Jewish life in food-from Shabbat and Mitzvah Moments, to J-Dating and Dinner with the Goyim In-Laws. Interspersed throughout are smart and funny short essays, line drawings, and photography of plated dishes and traditional memorabilia. Packed with homey recipes and relatable humor, this is as much a delicious, lighthearted, and nostalgic cookbook as it is a lively celebration of Jewish culture"--